ANALISIS PENGARUH STRUKTUR DAN MEKANISME GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP MANAJEMEN LABA - Putri, Intania Destiani; Sofian, Syuhada (Diponegoro Journal of Management, 2013)
Manufacture firms are in the stage of large enterprise companies that support the economy of the country. In the scope of manufacture emerged many new players that enhance competition by both new players and old players, so there is a big possibility to do earnings management.  This study aimed to examine the effect of Good Corporate  Governane  structure and mechanism,  firm size,  and  leverage  on earnings  management.  Good  Corporate  Governance  indicators  used  are institutional ownership, managerial ownership, the proportion of independent commissioners  and audit committee.This study uses secondary data, that was financial report of the companies in the manufacturing category listed on the Indonesia Stock Exchange. The sample used 19 companies in the  manufacturing  category  during  the  period  2007-2011.  The  analysis  method  used  is  OLS regression (Ordinary Least Square) with a significance level of 5%.Based on the results from ordinary  least square regression  analysis for six independent variables  showed  that  managerial  ownership  and  the  audit  committe  has  significant  effect  on earnings management, but managerial ownership has different direction with the hypothesis.While the institutional ownership, the proportion of independent comissioner, firm size and leverage does not influence earnings management.